1999
DOI: 10.1086/501601
|View full text |Cite
|
Sign up to set email alerts
|

Use of Personal Protective Equipment and Operating Room Behaviors in Four Surgical Subspecialties: Personal Protective Equipment and Behaviors in Surgery

Abstract: Akduman, Deniz; Kim, Lynn E.; Parks, Rodney L.; L'Ecuyer, Paul B.; Mutha, Sunita; Jeffe, Donna B.; Evanoff, Bradley A.; and Fraser, Victoria J., "Use of personal protective equipment and operating room behaviors in four surgical subspecialties: personal protective equipment and behaviors in surgery".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 12 publications
4
40
1
1
Order By: Relevance
“…9,10 Ame ri kan Has ta lık Kon trol ve Ön lem Mer kez le ri' nin (CDC) bu ön lem le rin uy gulan ma sı ge rek li li ği ni çok ön ce den bil dir me si ne ve stan dart ön lem le rin kan ve vü cut sı vı la rıy la te mas ris ki ni azalt tı ğı nın çe şit li ça lış ma lar da gös te ril mesi ne rağ men, sağ lık ça lı şan la rı nın bu ön lemle re uyu mu ye ter li de ğil dir. 3,9,[11][12][13] Sağ lık ça lı şan la rı -nın eği ti mi, stan dart ön lem le re uyu mu nun art tı rıl -ma sı ve te mas oran la rı nın azal tıl ma sı için ge rek lidir.…”
Section: Infectious Diseasesunclassified
“…9,10 Ame ri kan Has ta lık Kon trol ve Ön lem Mer kez le ri' nin (CDC) bu ön lem le rin uy gulan ma sı ge rek li li ği ni çok ön ce den bil dir me si ne ve stan dart ön lem le rin kan ve vü cut sı vı la rıy la te mas ris ki ni azalt tı ğı nın çe şit li ça lış ma lar da gös te ril mesi ne rağ men, sağ lık ça lı şan la rı nın bu ön lemle re uyu mu ye ter li de ğil dir. 3,9,[11][12][13] Sağ lık ça lı şan la rı -nın eği ti mi, stan dart ön lem le re uyu mu nun art tı rıl -ma sı ve te mas oran la rı nın azal tıl ma sı için ge rek lidir.…”
Section: Infectious Diseasesunclassified
“…Influence of the younger generation was perceived by respondents as one phenomenon that would increase the likelihood of PPE use. Akduman et al (1999) also found that generational differences influenced the use of PPE. In their study, medical students were more likely to wear goggles and residents were more likely to double glove.…”
Section: Discussion Of Research Questionsmentioning
confidence: 90%
“…Universal Precautions and PPE are only effective when used properly. Legally mandating the use of PPE through standards has not resulted in improved compliance (Akduman et al, 1999;Cutter & Jordan, 2004;Gershon et al, 1995;Nelsing, Nielsen, & Nielsen, 1997;Taylor, 2006). OSHA, in its bloodborne pathogens standard (1991), goes one step further than the CDC.…”
Section: Osha and Healthcarementioning
confidence: 99%
See 2 more Smart Citations